2017
DOI: 10.1111/jir.12440
|View full text |Cite
|
Sign up to set email alerts
|

Does differential visual exploration contribute to visual memory impairments in 22q11.2 microdeletion syndrome?

Abstract: This study is the first to investigate visual attention in 22q11.2DS during a memory task. The results delineate impaired processes during encoding that affect visual memory performance. The findings may be especially useful for informing interventions intended to boost visual learning in patients with 22q11.2DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…First, although stimuli were carefully selected, paying attention to floor or ceiling effects, the non-verbal task was more difficult than the verbal task. This was true for individuals with 22q11DS possibly influenced by specific deficits in visual analyses previously described (14,44), but also for the typically developing controls. Therefore, it is likely that the abstract nature of the chosen non-verbal stimuli generated an additional difficulty for all participants.…”
Section: Limitationsmentioning
confidence: 55%
See 2 more Smart Citations
“…First, although stimuli were carefully selected, paying attention to floor or ceiling effects, the non-verbal task was more difficult than the verbal task. This was true for individuals with 22q11DS possibly influenced by specific deficits in visual analyses previously described (14,44), but also for the typically developing controls. Therefore, it is likely that the abstract nature of the chosen non-verbal stimuli generated an additional difficulty for all participants.…”
Section: Limitationsmentioning
confidence: 55%
“…Furthermore, previous results have shown that the degree of impairment in non-verbal memory tasks varies depending on the type of stimuli, with greater deficits for more abstract or complex material (e.g., faces or landscape vs. dot localization) ( 13 ). A study using eye-tracking showed atypical exploration strategies (more time spent in the center of the image, less on the peripheral details), leading to sub-optimal encoding and subsequently poorer memory performance ( 14 ). Only few studies investigated encoding in 22q11DS using drawings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results might suggest that the eye-tracking measures used in the current study are insufficient for understanding task performance. Other mechanisms such as idiosyncratic scanning strategies and encoding process of visual stimuli and visual memory of faces could also contribute to their performance [ 63 , 65 , 66 ]. Future research should consider the use of the Dynamic Scanning Index (reflecting the number of times that the eye gaze goes in and out of a core feature) that might better reflect task performance [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…On a behavioral level, a dissociation between verbal and visual memory processes has been described in 22q11DS. Indeed, probably due to poorer visuospatial and visuo-attentional processes, visual memory acquisition is not optimal and visual memory is generally reported as impaired (Bostelmann, Glaser, Zaharia, Eliez, & Schneider, 2017;Lajiness-O'Neill et al, 2005;Woodin et al, 2001). By contrast, it has been argued so far that verbal memory stands out as a relative strength in the 22q11DS cognitive profile (Jacobson et al, 2010;Lajiness-O'Neill et al, 2005;Lewandowski, Shashi, Berry, & Kwapil, 2007).…”
Section: Introductionmentioning
confidence: 99%